Desenho como método de composição sobre criaturas ficcionais biomecânicas - Ferreira, Nuno Vieira da Silva Tomé (2020)
The present dissertation provides an investigation that uses drawing as a composition method to deepen the knowledge about fictional creatures composed of two materials with different origins. Organic and mechanical. The purpose is to structure a constructive methodology that serves as an example to follow for the creation of biosynthetic fictional living beings, based on concept art drawings. Consequently, the theoretical aspect of this research describes the form of drawing used, as well as the method of how these creatures will be demonstrated through concept art. Afterwards the catalyst inspiration of these fictional creatures is deepened, where their idea was originally contextualized, which is through science fiction. In this sense, some artists who produce art associated with the subject of biomechanics are exemplified, as well as creatures from film and video game media, to be based on and analyzed for the composition of the creatures present in this dissertation. Regarding the practical approach of this work, it is deepened and reflected the issue of the creation, exploration and visual patterns of these fictional creatures, as these are crucial aspects to develop for their design. From there, it is demonstrated the creative process that encompasses the studies and research of the drawings made as well as its development. Then in the final realization of the developed creatures, the entire practical archived process is demonstrated through the digital drawings made. From the silhouette chosen for each creature, the initial sketches, line drawing and color of the final appearance, as well as drawings showing all the general physiognomy and shapes that some creatures have. A description of each creature is also given, mentioning what kind of place and function they have in the fictional society in which they find themselves.